2020
DOI: 10.1097/md.0000000000022178
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of postmenopausal osteoporosis and interventive mechanism of catgut embedding in acupoints

Abstract: Introduction: Postmenopausal osteoporosis (PMOP), which is a common and frequently occurring age-related metabolic bone disease in perimenopausal women, severely affects patients living quality. Modern medicine therapies for PMOP have several problems such as side reactions, low compliance, and high costs. Thus, nonpharmacological modality is urgently needed. Although acupoint thread embedding treatment is widely used in clinical practice, there is no persuasive evidence of its effect on increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…We compared the effects of ACE and EA on BMI data. [15,25,28,36,40,43,46,47,52,53,63,65,74,82,83,86,87] There was no significant difference between the two groups (n = 1246, MD = 0.18 [−0.85, 1.21]; P = .73, I 2 = 20%).…”
Section: Bwmentioning
confidence: 92%
See 3 more Smart Citations
“…We compared the effects of ACE and EA on BMI data. [15,25,28,36,40,43,46,47,52,53,63,65,74,82,83,86,87] There was no significant difference between the two groups (n = 1246, MD = 0.18 [−0.85, 1.21]; P = .73, I 2 = 20%).…”
Section: Bwmentioning
confidence: 92%
“…Total effective rate. Twenty-four studies [15,25,28,30,36,40,41,43,46,47,[52][53][54]59,63,65,71,74,79,82,83,86,87,91] reported data on ACE versus EA. The result showed a significant difference between ACE and EA (n = 1825, RR = 1.06 [1.02, 1.10]; P = .005, I 2 = 24%) (Fig.…”
Section: 321mentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous studies have revealed that moxibustion may alleviate osteoporosis pain, improve BMD, and reduce the response rate, among others. Moreover, some previous studies [17][18][19][20][21][22] have shown that moxibustion can improve BMD, bone strength, and hormone levels, effectively increasing the vitamin D level in serum. Moxibustion also improves bone calcium content and BMD by regulating calcium and phosphorus metabolism.…”
Section: Introductionmentioning
confidence: 99%